Supervisory objectives, practices and teachiques in the elementary schools of the province of Romblon - Platon, Lauro S. 1912- (Quezon City, Philippines College of Education, University of the Philippines Diliman, 1965)
This study determines the objectives of the supervisors in their supervision of elementary schools and the practices and techniques they employ in supervision. It aims at the improvement of supervision in the elementary schools in the division.
Thesis (Master of Education)--University of the Philippines, Diliman
Keywords: School supervision, Elementary -- Romblon (Philippines : Province).